تحديد بعض المواصفات الجيوهندسية للترب الغضارية المستخدمة في إنشاء السدود الترابية : سد الوغر التجميعي في منطقة النبك) - عيسى محمد; السبتي حذيفة (Latakia University Journal -Basic Sciences Series, 2013)
تكمن القيمة العلمية والعملية لهذا البحث في التعرف على مواصفات الترب الغضارية الموجودة في منطقة النبك, وإمكانية استخدامها في إنشاء سد الوغر التجميعي. وقد تمت الدراسة على خمس عينات تم اختيارها من مقلع حفر الملاجئ الغضاري الذي سيستخدم في انشاء سد الوغر التجميعي, تم من خلالها تحديد بعض المواصفات الجيوهندسية لهذه الترب وأهمها (حد السيولة – حد اللدانة – دليل اللدانة - دليل القوام والسيولة – فعالية الغضار – درجة الانهياريه). وبالاعتماد على نتائج هذه الدراسة استخدمنا التصنيفات العالمية ( تصنيف كازاغراندي – نظام التصنيف الموحد – التصنيف الأمريكي والروسي حسب دليل اللدانة ) لدراسة ترب المنطقة المراد دراستها. واعتمدنا نتائج الدراسة لتحديد موقع هذه الترب وفقا للتصنيف العالمي, واقترحنا بعض الحلول المناسبة لتحسين خواص الترب المستخدمة في تشييد السدود الترابية. The scientific and practical value of this research appears in recognizing the characteristics of the clay soil, which is located in Alnabeck, and used in constructing ALwagar earth fill dam. We will study five samples chosen from the materials site Hofar ALmlagea and which will be used in constructing ALwagar earth fill dam through which some Geo-geometrical characteristics like (Liquid Limit, Plasticity Limit, plasticity index, Consistency Index, Liquidity Index, Clay activity, collapse degree) will be determined. Depending on the Results of this study, we used international classifications (Casagrande classification – Unified Soil Classification System) to study the soil of the studied area. We made use of the results of the experimental study to determine the position of soil according to the international classification, and we suggested some solutions to improve the characteristics of the soil which is used in constructing soil dams.